The Meaning of Traditional Food in Building the Identity of the Banjar People - Rochgiyanti Rochgiyanti; Yuli Apriati; Fathurrahman Fathurrahman; Four Steven Lase; Yarni Ester Gea; Amandita 'Ainur Rohmah (Universitas Sebelas Maret, 2026)
Modernization and changes in societal lifestyles have caused traditional cuisine to become increasingly marginalized and at risk of disappearing among younger generations. This study aims to analyze the meanings of traditional food in building the resilience of Banjar community identity. The research employs a qualitative method with an ethnographic approach. Data were collected through participant observation, in-depth interviews using purposive sampling techniques, and visual documentation, which were then analyzed thematically. The findings indicate that Banjar traditional foods possess four dimensions of meaning that strengthen identity resilience: (1) symbolic meanings embedded in customary and religious rituals that reinforce spiritual and cultural values; (2) meanings as markers of identity and collective pride; (3) ecological meanings that reflect harmonious human–environment relations and local wisdom; and (4) meanings as a medium for intergenerational transmission of values and character education. The preservation of Banjar traditional food constitutes a cultural strategy for sustaining identity in the era of modernization, as well as a form of cultural capital for the development of sustainable gastronomic tourism.